Digitalização do trabalho no INSS: tensões e estratégias de regulação na implementação do novo modelo de atendimento - Sacha Pinheiro; Marta Santos; Liliana Cunha (Universidade do Porto, 2018)
The scope of this paper is the digitalization of the service at the National Institute of Social Security - INSS, the federal institution in charge of implementing the Brazilian Welfare Services policy. Based on the framework of Work Psychology and Activity-centered Ergonomics, a field study has been carried out in order to understand the conditions under which the "Digital INSS Project" has been implemented and their impact on the activity performed by the public servants. It revealed the heterogeneity in terms of production control and resources to enable the appropriation of technological tools by the workers from different units. Given the intensification of work, the regulatory strategies try to balance the production demands and the health preservation. They do so through schemes to use the computer tools that confront these workers with additional workload, given the accomplishment of several simultaneous operations and the necessity to validate the work using paper, in the face of the unexpected generated by the digital support and the experience still to be built in its resolution.